Management of post-midurethral sling voiding dysfunction. International Urogynecological Association research and development committee opinion. (January 2018) - Bazi, Tony; Kerkhof, Manon; Takahashi, Satoru; Abdel-Fattah, Mohamed
Abstract Voiding dysfunction following midurethral sling procedures is not a rare event. There is no current consensus regarding management of this complication. Although it is often transient and self-limiting, chronic post-midurethral sling voiding dysfunction may lead to irreversible changes affecting detrusor function. Initial management includes intermittent catheterization, and addressing circumstantial factors interfering with normal voiding, such as pain. Early sling mobilization often resolves the dysfunction, and is associated with minimal morbidity. Sling incision or excision at a later stage, although fairly effective, could be associated with recurrence of stress urinary incontinence. There is insufficient evidence to justify urethral dilatation in this context.